A Study Of Vocational School Teacher Preferences And Readiness To Form A Learning Community With The Collaborative Teacher Inquiry Approach - Mian Siahaan; Elisabeth Batubara (STABN RADEN WIJAYA WONOGIRI, 2025)
This study aims to analyze the preferences and readiness of vocational high school (SMK) teachers in Medan City to form a learning community based on Collaborative Teacher Inquiry (CTI). A mixed-methods sequential explanatory approach was employed, involving 250 quantitative respondents and 9 in-depth interview participants. The findings indicate that Learning Goal Orientation (LGO) is a significant predictor of CTI readiness (β = 0.216, p < 0.001), with systemic barriers acting as a key mediator. Teacher preferences for collaborative learning were reflected in a strong interest in small discussion groups (78%) and flexible scheduling. This study proposes a contextualized CTI model tailored to the needs of vocational teachers, strengthening the role of LGO as a resilience mechanism for overcoming structural challenges